Structure of isophthalic acid based monolayers and its relation to the initial stages of growth of metal-organic coordination layers - Shen, Cai; Zhao, Jianli; Zharnikov, Michael (Chemical science, 2012)
Self-assembled monolayers (SAMs) of isophthalic acid (IPA) and trimesic acid (TMA) formed on Cu modified Au(111) substrates by adsorption from aqueous solution were characterised by synchrotron-based X-ray photoelectron spectroscopy (XPS), near-edge X-ray absorption fine structure spectroscopy (NEXAFS) and scanning tunneling microscopy (STM). Applying the layer-by-layer (LbL) method, the initial stages of growth of metal-organic coordination layers from Cu-acetate and TMA has been studied by STM. Both IPA and TMA SAMs exhibit a row structure with the aromatic units tilted by about 45° with respect to the surface normal. The average distance between rows is 3 × Au-Au distance (= 8.67 Å) with, however, slight variations between different rows. For IPA a very regular pattern is observed giving rise to a rectangular (9 × √3) unit cell containing three molecules. Combining all data a structure is suggested where the molecules are tilted and azimuthally rotated. The variation in the inter-row distance is explained by correlated tilts and rotations in opposite directions. STM studies of the first two LbL deposition cycles reveal predominantly disordered nucleation at domain boundaries. The observation of epitaxial features is explained to arise from a particular combination of molecular orientation in adjacent rows.